Stability Order of the Conformations and Relative Intramolecular Hydrogen Bond Studies of 4-Hydroxy-3-(1-hydroxyvinyl)-pent-3-ene-2-one - Arabali, Vahid; Amel-Mehrabi, Ebrahim; Zare, Karim (Asian Journal of Chemistry, 2010)
B3LYP method was applied for a complete study of 4-hydroxy-3- (1-hydroxyvinyl)-pent-3-ene-2-one and gaining the stability order of the conformations and relative intramolecular hydrogen bond strengths among 13 different possible conformers of this system.